2019
DOI: 10.1021/acsabm.9b00060
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hydrogel Cross-Linking Chemistry on the in Vitro and in Vivo Bioactivity of Recombinant Human Bone Morphogenetic Protein-2

Abstract: Designing strategies to deliver functional proteins at physiologically relevant concentrations using chemically cross-linked biocompatible hydrogels is a major field of research. However, the impact of cross-linking chemistry on the encapsulated protein bioactivity is rarely studied. Here we examine the two well-known cross-linking reactions namely; hydrazone cross-linking chemistry and thiol-Michael addition reaction to form hyaluronic acid (HA) hydrogels. As a therapeutic protein, we employed recombinant hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…Thus, the properties of scaffolds have been improved by chemical cross-linking, but this procedure often requires chemical modification or prior chemical treatment with reactive functional groups. 30 33 This can be associated with cytotoxicity and require extensive purification. Therefore, an alternative process, namely, dehydrothermal (DHT) treatment in the dry state after PEC can be considered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the properties of scaffolds have been improved by chemical cross-linking, but this procedure often requires chemical modification or prior chemical treatment with reactive functional groups. 30 33 This can be associated with cytotoxicity and require extensive purification. Therefore, an alternative process, namely, dehydrothermal (DHT) treatment in the dry state after PEC can be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Scaffolds based on CMC and CS have been prepared via polyelectrolyte charge complexation (PEC) followed by freeze-drying and reported for tissue engineering applications. , Even though they can easily be fabricated via PEC, most products lack dimensional stability or load-bearing capacity in biological environments under physiological conditions (37 °C, pH 7.4). Thus, the properties of scaffolds have been improved by chemical cross-linking, but this procedure often requires chemical modification or prior chemical treatment with reactive functional groups. This can be associated with cytotoxicity and require extensive purification. Therefore, an alternative process, namely, dehydrothermal (DHT) treatment in the dry state after PEC can be considered.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that proteins can be encapsulated in similar PEG hydrogels without causing structural changes or aggregation (Zustiak & Leach, 2010, 2011). Contrarily, others have shown that proteins might interact with functionalized PEG during gelation via nucleophilic reactions with α,β‐unsaturated carbonyl compounds, disruption of disulfide bridges from thiol‐functionalized polymers, or hydrophobic interactions (Hammer et al, 2015; Paidikondala et al, 2019). Note that lysozyme has four disulfide bonds and a relatively hydrophobic surface and may be susceptible to such interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the field of bone tissue engineering have recently showed that the incorporation of bone morphogenetic protein (BMP) as a growth factor into the hydrogels can promote in vivo bone formation on the implants’ surface [ 69 ]. Li et al constructed a porous Ti alloy (Ti-6Al-4V) and injected BMP-laden chitosan TRHs into pores of the Ti6Al4V scaffolds [ 70 ].…”
Section: Temperature-responsive Hydrogels (Trhs)mentioning
confidence: 99%